2013
DOI: 10.1038/bjc.2013.734
|View full text |Cite
|
Sign up to set email alerts
|

Is lack of surgery for older breast cancer patients in the UK explained by patient choice or poor health? A prospective cohort study

Abstract: Background:Older women have lower breast cancer surgery rates than younger women. UK policy states that differences in cancer treatment by age can only be justified by patient choice or poor health.Methods:We investigate whether lack of surgery for older patients is explained by patient choice/poor health in a prospective cohort study of 800 women aged ⩾70 years diagnosed with operable (stage 1–3a) breast cancer at 22 English breast cancer units in 2010–2013. Data collection: interviews and case note review. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 44 publications
5
56
1
2
Order By: Relevance
“…The analysis demonstrates that increasing age at diagnosis is associated with a reduced likelihood of receiving surgical treatment which is consistent with other similar studies (5,15,(23)(24)(25)(26) . Deprivation level was also associated with treatment type, with the most deprived group being less likely to undergo surgical management, a finding also described by Lavelle and colleagues in their prospective cohort of 800 women (26) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The analysis demonstrates that increasing age at diagnosis is associated with a reduced likelihood of receiving surgical treatment which is consistent with other similar studies (5,15,(23)(24)(25)(26) . Deprivation level was also associated with treatment type, with the most deprived group being less likely to undergo surgical management, a finding also described by Lavelle and colleagues in their prospective cohort of 800 women (26) .…”
Section: Discussionsupporting
confidence: 90%
“…Deprivation level was also associated with treatment type, with the most deprived group being less likely to undergo surgical management, a finding also described by Lavelle and colleagues in their prospective cohort of 800 women (26) . This may be due to the fact that affluence is associated with lower levels of comorbidity and smoking, and greater longevity and education (27) , thereby promoting better health and discussion of treatment options.…”
Section: Discussionsupporting
confidence: 63%
“…Several studies have explored the issue of increasing age ei g asso iated ith u de t eat e t of older women with operable breast cancer [5,[23][24][25]. Our results show that whilst HCPs consider age one of the least important factors in determining which treatment options to offer, it remains important and several interview participants admitted to using age-specific cut-offs to determine who should be offered PET.…”
Section: The Uk S Depa T E T Of Health Esta Lished the Natio Al Ca mentioning
confidence: 79%
“…However, a recent study by Lavelle and colleagues [23] found that lower rates of surgical treatment are unlikely to be due to patient choice and these results suggest that UK HCPs agree with this, believing that patients would not choose non-operative management if given the option. Hamaker and colleagues [15] suggested that variation in treatment may reflect underlying clinician preference influencing communication of treatment options.…”
mentioning
confidence: 99%
“…It is possible that their view of the decision making process represents the lack of an imposed treatment by the doctor but may still reflect the preference of the doctors or other HCP [31]. The impact of patients' choice on surgical rates in older women was investigated by Lavelle and colleagues [32] who conclude that actively opting out of surgery is unlikely to be the reason fewer older women undergo surgery. This study found older women wish to be active decision makers with women frequently reporting making an instant decision about their treatment choice either before a confirmed diagnosis or immediately after.…”
Section: Discussionmentioning
confidence: 99%